Revealing the traditional music of Gamelan: A mathematical content for elementary students - Ainora, Eva Pungki; Utami, Niken Wahyu (Journal of Honai Math, 2024)
Gamelan, a traditional Indonesian musical ensemble, presents an intriguing avenue for integrating mathematical concepts into elementary school curricula. This study employs an ethnomathematics approach to unveil the inherent mathematical principles embedded within Gamelan compositions, aligning them with elementary mathematical content. Through participant observation, interviews with practitioners, and document analysis, the research elucidates Gamelan's potential to facilitate learning across various mathematical domains. Findings indicate that Gamelan can effectively convey geometric concepts such as squares, rectangles, circles, spheres, trapezoids, cylinders, and cones, as well as principles of measurement utilizing standard units and numerical operations through tangible, experiential methods.